(3GdJhGRf Hjf GdSdWJjf GdJTQjYjI hGdJfajPjI aj OhdI GdchjJ (B: s (3OQGSI ebGQfI (B/ s - (3PcQi YGjO YhV GdQTjOj s; (3jMjj GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3dbO YGfJ GdTYhH GdYQHjI ef JbjjO MQjGJ GdeeGQSI GdOjebQGWjI ai GdYed GdHQdeGfj Ch ai UjGZI fUh OSJhQjI JcHdgG (B: (3hef Gdege ai ehGRGI Pdc Cf jJMbb GdJhGRf Hjf GdSdWJjf GdJTQjYjI hGdJfajOjI hGdPi jMbb HGdJGdj GdGSJbQGQ GdSjGSj GdefThO dJMbjb GdGUdGM adG JWZj SdWI Ydi SdWI HGNJUGUGJgG aJbjOgG Yf eeGQSI OhQgG GdefhW (B: (3hdG JSQa SdWI ai GNJUGUGJgG aJJMhd Jdc GdGNJUGUGJ gOeG Ohf HfGA (B. (3hef Cge eG jJhLH GdbjGe Hg ef CLd JCUjd ZGjI GdeTQY GdOSJhQj ef JhRjY GdGNJUGUGJ dJMbjb GdJhGRf Hjf GdSdWI GdJTQjYjI hGdJfajPjI (B: (3gh GjLGO fUhU JMOO cjajI JMOjO GdChdhjGJ ai JhGRf eJcGaiA (B: (3hCf dG jJNe LOhd CYeGd GdHQdeGf HLGJH hjged BNQ(B: (3adG jYWZi GdOhQ GdJTQjYi Ydi GdQbGHj (B: (3hdG GdGSJLhGH Ydi GdSDGd (B: (3aJfbdH GdeaGgje (B: (3hjNJd ejRGf GdJOQL ai GdQbGHI(B: (3hdG Cf jJe GdGSQGa ai dLGf GdJMbjb aJabO bjeI CKQgG hJKbd GdegGe GdHQdeGfjI (B: (3ai bVGjG jecf Cf JHMK ai EWGQ BNQ (B: (3hdGHO ai gPG GdNUhU Cf JMJQe GdehGYjO GdOSJhQjI hGddGFMjI (B: (3hGdbhGYO hGdTQhW (B: (3adG jchf ddGLJgGO eMdG eY hVhM GdfUhU(B: (3hdG JaSQ GdfUhU GdOSJhQjI HYjOG Yf ebGUOgG JChjdG dejhd fjGHjI Ch JhLgGJ MchejI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B562-586s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdQbGHI GdeJHGOdI s; (3GdSDGd GdHQdeGfjs; (3JhRjY GdGNJUGUGJ s; (3GdaUd Hjf GdSdWGJs; (3GYeGd GdHQdeGfs; (3GNJUGU GdHQdeGfs; (3GdSDGd GdHQdeGfis; (3GdeSFhdjg GdhRGQjg GdSjGSjgs; (3JhRjY GdGNJUGUGJs; (3GdbGfhf GdchjJis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes